Spasi Artistik Interaktif untuk Anak (SAIA): Creative Business Model Proposal for Children's Interactive Art Space and Art Therapy - Augustin, Elfitra Mercredi; Larso, Dwi (The Indonesian Journal of Business Administration, 2013)
Plato, the Greek philosopher once opined that "Art is supposed to be part of basic education or should be the foundation of education, because art, to a certain extent, it forms our personality sharpen the mind and character." This indicates that art has a very strong influence in the formation of human character, especially if introduced in early stage. On one hand, Art is also considered as an effective mental health treatment. In psychotherapy often used as an expressive medium to help clients communicate, cope stress and explore more in various personality aspects. Art therapy may eventually be an option for children with special needs. The need for a location that serves as a children's art community and the availability of art therapy in Indonesia seen quite possible. This thesis is to focus on the proposal / initiation of a creative social business model that has Value Proposition as a Children's Interactive Art Space and Art Therapy called Spasi Artistik Interaktif untuk Anak (SAIA). For limited source of information, the analysis be done by benchmarking against some overseas locations that have the same vision and mission as well as analyzing the needs of the external environment in Indonesia through interviews with experts and literature study. It resulted in how Children's Art Space and Art Therapy can be a very promising field to be implemented in Indonesia and a well-strategic plan is needed to overcome its weaknesses of lacking in initial capital and art therapist resources. Solution is generated by using Business Model Canvas to create a creative business model proposal that suits with the need and environment in Indonesia. With parents and children and/or children with special needs as the main Customer Segment, SAIA has three main Key Activities which are Art Space, Art Therapy and ArtCubator. Using Lovermarks style of Customer Relationship, Revenue Streams is generated from classes, workshops, art therapy and lease of space. Physical, human and financial as SAIA's Key Resources; and partnership with numerous organizations, companies, medias, foundation related with children, art, social and education. Implementation of the business model will be placed on the consolidation of all aspects in the Business Model Canvas into 18 month development process strategy which include a series of program like DSUSFellowship, Stack Them Up and Spread The News.Â Keywords: business models, art space, art therapy, children, children with special needs.